ANALISIS PEMBENTUKAN PORTOFOLIO PADA PERUSAHAAN YANG TERDAFTAR DI LQ45 DENGAN PENDEKATAN METODE MARKOWITZ MENGGUNAKAN GUI MATLAB - Titin Afriana; Tarno Tarno; Sugito Sugito (Jurnal Gaussian, 2017)
Portfolio is one of  ways  in investment activity that  undertaken by more than one asset with intent to determining the amount of proportion of investment  that to be made in a certain period of time. To determine optimal portofolio, one of  analysis model which can be played is Markowitz. Markowitz exressed through diversification concept (with  making of the optimal stock of  portfolio), investor can maximize the expected income from investments with specific risk level or seeking to minimize risk to target certain profit level. To simplify the calculation of the portfolio for  public, there is an application that made by using GUI in Matlab. Matlab (Matrix Laboratory) is an interactive programming system with  basic elements of array database which dimensions do not need to be stated in a particular way, while the GUI is the submenu of Matlab. Generally, Matlab GUI is  more easily learned and  used because  it worked without  need to know  the commandments and how the command works. The data used in this study consists of five types of assets in the LQ45 group, there are BBNI,  PWON, PTBA, INCO, dan KLBF. In determining the portfolio proportion used trial and error method and Lagrange method. Based on the portfolio proportion of both methods obtained the optimal portfolio is almost the same. Keywords: GUI Matlab, LQ45, Portfolio, Markowitz, Trial and Error, Lagrange